Green certificates: A better version of green bonds - Dion Bongaerts; Dirk Schoenmaker (Bruegel, 2020)
-The market for green bonds is growing rapidly and has been boosted by the European Commission's plan to raise through green bonds 30 percent of the up to exteuro750 billion that will be borrowed under the Next Generation EU coronavirus economic recovery programme. But while green bonds can reduce the financing costs of green projects and technologies, their current design means they fall short of fulfilling their full potential. Issuing green bonds alongside regular bonds fragments bond issues, reducing liquidity and thus increasing financing costs. Moreover, green bond prices reflect liquidity, credit risk and environmental performance jointly, which makes it difficult to isolate the part of the return on the bonds that relates to environmental performance. -We propose an alternative: issuance of regular bonds with attached green certificates that ensure earmarking for green purposes. The new design would lead to more liquid securities (as only regular bonds are issued), which would reduce financing costs and in turn would provide incentives to start a greater number of environmentally-friendly projects. The new design would also make market prices more informative about environmental performance. In addition, green certificates would address the criticism that green bonds are used mostly for refinancing existing green projects rather than for new projects. -Sovereigns are among the largest issuers of bonds and are therefore natural candidates for implementation of green certificates. The European Commission could also issue regular bonds and green certificates to finance the European Union's recovery package, and should include green certificates in the under-preparation EU Green Bond standard. Commission issuance of green certificates would give a major boost to EU bonds as liquid safe assets while promoting green investment.
Keywords: 330